2016
DOI: 10.1159/000447910
|View full text |Cite
|
Sign up to set email alerts
|

WIN 55,212-2 Inhibits the Epithelial Mesenchymal Transition of Gastric Cancer Cells via COX-2 Signals

Abstract: Background: Cannabinoids (the active components of Cannabis sativa) and their derivatives have received considerable interest due to reports that they can affect the tumor growth, migration, and metastasis. Previous studies showed that the cannabinoid agonist WIN 55,212-2 (WIN) was associated with gastric cancer (GC) metastasis, but the mechanisms were unknown. Methods: The effects of WIN on GC cell migration and invasion were analyzed by the wound-healing assay and Transwell assay. Quantitative real-time PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The metastasis of epithelial tumors involves a series of phenotypic changes, known as the EMT. Cannabinoids have been reported to inhibit EMT in gastric, endometrial and NSCLC cancer cells [4,34,51]. However, this important property of cannabinoids has not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The metastasis of epithelial tumors involves a series of phenotypic changes, known as the EMT. Cannabinoids have been reported to inhibit EMT in gastric, endometrial and NSCLC cancer cells [4,34,51]. However, this important property of cannabinoids has not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, A549, H460 and H1792 cells were exposed to 20 ng/ml EGF in order to analyze cell migration, as previously reported [34]. As summarized in Fig 5, EGF induces cell migration in the three types of cancer cell used.…”
Section: Cannabinoids Inhibit Egf-induced Cell Motility In Cancer Cellsmentioning
confidence: 93%
See 1 more Smart Citation
“…Various drugs have been intensively researched in many animal experiments and clinical trials for gastric cancer [33, 34]. Some studies have indicated that chemopreventive compounds in dietary foods are a potential source of safe bioactive compounds for cancer chemoprevention and suppression of proliferation via the primary target of ROS that damages DNA and the activation of signaling pathways, as well as the expression of proteins involved in the induction of apoptosis [12, 13, 19].…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 has been reported to be a mediator of TGF-β1-induced EMT (24). However, whether it plays a key role in EMT induced by TGF-β1 in TCC has not been clarified.…”
Section: Cox-2 Upregulation Is Essential For Tgf-β1-induced Emtmentioning
confidence: 99%